2018
DOI: 10.1007/s12975-018-0620-4
|View full text |Cite
|
Sign up to set email alerts
|

Human Ischaemic Cascade Studies Using SH-SY5Y Cells: a Systematic Review and Meta-Analysis

Abstract: Low translational yield for stroke may reflect the focus of discovery science on rodents rather than humans. Just how little is known about human neuronal ischaemic responses is confirmed by systematic review and meta-analysis revealing that data for the most commonly used SH-SY5Y human cells comprises only 84 papers. Oxygen-glucose deprivation, H2O2, hypoxia, glucose-deprivation and glutamate excitotoxicity yielded − 58, − 61, − 29, − 45 and − 49% injury, respectively, with a dose-response relationship found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 36 publications
0
43
0
Order By: Relevance
“…Since there are several studies using this cell line as an in vitro model for neurodegenerative disorders (Liu et al, 2018;Murillo et al, 2017;Xicoy, Wieringa, & Martens, 2017), particularly for investigation of Aβ toxicity and drug screening (Jämsä, Belda, Edlund, & Lindström, 2011;Lattanzio, Carboni, Carretta, Candeletti, & Romualdi, 2016;Yuan et al, 2017), our first objective was to compare the effect of the peptide on undifferentiated and differentiated cells. SH-SY5Y are neuroblast-like cells that can be differentiated into a mature neuronal phenotype using several differentiating agents, including RA, phorbol esters, and neurotrophins (Kovalevich & Langford, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Since there are several studies using this cell line as an in vitro model for neurodegenerative disorders (Liu et al, 2018;Murillo et al, 2017;Xicoy, Wieringa, & Martens, 2017), particularly for investigation of Aβ toxicity and drug screening (Jämsä, Belda, Edlund, & Lindström, 2011;Lattanzio, Carboni, Carretta, Candeletti, & Romualdi, 2016;Yuan et al, 2017), our first objective was to compare the effect of the peptide on undifferentiated and differentiated cells. SH-SY5Y are neuroblast-like cells that can be differentiated into a mature neuronal phenotype using several differentiating agents, including RA, phorbol esters, and neurotrophins (Kovalevich & Langford, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Differentiated SH-SY5Y are widely accepted for in vitro experiments requiring neuronal-like cells. 17…”
Section: Cell Culture and Treatmentsmentioning
confidence: 99%
“…The present study was undertaken to determine the roles of APE1 in the protective effects of curcumin against cerebral I/R injury, as well as to identify the molecular mechanisms through which curcumin affects SH-SY5Y neuronal cells subjected to oxygen-glucose deprivation/reperfusion (OGd/R), a commonly used in vitro model of cerebral I/R injury (24,25). It was observed that curcumin protected the SY-SH5Y cells against OGd/R injury by upregulating APE1 expression, which is associated with the regulation of the phosphatidylinositol 3-kinase/protein kinase B (PI3K/AKT) signaling pathway.…”
Section: Curcumin Exerts Protective Effects Against Hypoxia-reoxygenamentioning
confidence: 99%